Comparison of the efficacy between topical diquafosol and artificial tears in the treatment of dry eye following cataract surgery: A meta-analysis of randomized controlled trials. Issue 39 (September 2017) - Zhao, Xinyu; Xia, Song; Chen, Youxin
Abstract: Background: The prevalence of dry eye following cataract surgery was reported as high as 55.7%, this acute and iatrogenic disorder urgently required appropriate clinical management. The purpose of this study is to compare the efficacy of diquafosol sodium ophthalmic solution (DQS) and conventional artificial tears (AT) for the treatment of dry eye following cataract surgery. Methods: The PubMed, Embase, and the Cochrane Central Register of Controlled Trials were searched from their earliest entries through June 2017 to obtain the studies, which evaluated the efficacy of DQS for patients with dry eye after cataract surgery. The relevant data were analyzed using StataSE 12.0 software. The PRISMA checklist was used as protocol of the meta-analysis and the guideline was followed. The weighted mean difference, relative risk, and their 95% confidence interval were used to assess the strength of the association. Results: The authors identified 21 references of which 4 studies evaluating the efficacy of DQS for patients with dry eye after cataract surgery were included. The dataset consisted of 291 patients of dry eye following cataract surgery (371 postoperative eyes). The pooling result of our study suggested that the DQS could significantly better improve the indices like corneal and conjunctival fluorescein staining scores, tear breakup time, and Schirmer I test than AT ( P < .05). Although the scores of symptom questionnaire could not be pooled, the results of each study also proved that DQS could significantly better relieve the symptoms of postoperative dry eye. Conclusion: Based on the available evidence, topical DQS has a superior efficacy than AT in the management of dry eye after cataract surgery; however, further researches with larger sample sizes and focus on indicators such as higher-order aberrations, symptom questionnaire scores, and cost-effective ratio are required to reach a firmer conclusion.